2021
DOI: 10.1038/s41467-021-23526-w
|View full text |Cite
|
Sign up to set email alerts
|

Giant enhancement of THz-frequency optical nonlinearity by phonon polariton in ionic crystals

Abstract: The field of nonlinear optics has grown substantially in past decades, leading to tremendous progress in fundamental research and revolutionized applications. Traditionally, the optical nonlinearity for a light wave at frequencies beyond near-infrared is observed with very high peak intensity, as in most materials only the electronic nonlinearity dominates while ionic contribution is negligible. However, it was shown that the ionic contribution to nonlinearity can be much larger than the electronic one in micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 53 publications
2
31
0
Order By: Relevance
“…Over the past decades, numerous techniques have been developed to enhance THz generation efficiency, achieve narrow THz bandwidth, and decrease THz-wave decay in LN crystals 31 33 . In particular, it has been recently shown that giant enhancement of the optical nonlinearity can be achieved at THz-frequencies by stimulated phonon-polaritons in LN crystals pumped by a femtosecond laser pulse, where ionic contributions to light–matter interaction become significant 11 . While the underlying mechanisms under different excitation conditions merit further investigation, it is experimentally evident that tunable THz pulses can be generated in nonlinear LN crystals by means of ultrashort laser pulses in the range from a few tenths of THz to a few THz 11 , 31 , 32 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Over the past decades, numerous techniques have been developed to enhance THz generation efficiency, achieve narrow THz bandwidth, and decrease THz-wave decay in LN crystals 31 33 . In particular, it has been recently shown that giant enhancement of the optical nonlinearity can be achieved at THz-frequencies by stimulated phonon-polaritons in LN crystals pumped by a femtosecond laser pulse, where ionic contributions to light–matter interaction become significant 11 . While the underlying mechanisms under different excitation conditions merit further investigation, it is experimentally evident that tunable THz pulses can be generated in nonlinear LN crystals by means of ultrashort laser pulses in the range from a few tenths of THz to a few THz 11 , 31 , 32 .…”
Section: Resultsmentioning
confidence: 99%
“…In order to realize the proposed THz field manipulation, we perform a series of experiments with a typical pump-probe setup 11 to obtain both the dispersion curves of the structure at different z -positions (Fig. 3 , first row) and the energy distributions of the confined modes (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Research on phonon–polaritons mainly include two regimes, one in the van der Waals materials , and the other in the bulk ionic crystals, based on the material they are explored in. In very recent studies, the topological transition of phonon–polaritons in twisted stacks of two-dimensional materials (such as α-MoO 3 ) , and gratings were experimentally studied, but the topological edge transport of phonon–polaritons in the ionic crystals still remains a fertile ground to be explored.…”
Section: Phonon Polaritons and The Master Equationmentioning
confidence: 99%